HUBUNGAN PEMAKAIAN MASKER N95 DAN MASKER BEDAH TERHADAP KEJADIAN ACNE VULGARIS PADA TENAGA MEDIS DI RUMAH SAKIT UMUM DAERAH PENYABUNGAN - ERLIANI ERLIANI; RIRI ARISANTY SYAFRIN LUBIS (LP2MTBM MAKARIOZ, 2023)
At the end of 2019, precisely in December, a new type of coronavirus was discovered, namely SARS COV 2 and was named Coronavirus Disease 2019 (COVID 19). Several experiments have shown that wearing surgical masks and N95 can protect the wearer from contracting the virus and transmitting the virus to others. The use of masks in the long term can cause problems on the skin including the emergence of , dermatitis, redness and pigmentation on the face. Maskne or Mask- is a term used when skin conditions are -prone and irritated in areas that are often covered by masks, namely in the nose to the chin area. To determine the relationship between the use of N95 masks and surgical masks on the incidence of acne vulgaris in medical personnel at Panyabungan Hospital. Analytical descriptive with a cross sectional study design where data collection was only done once and there was no follow-up to the sample. The data in this study were obtained from primary data through filling out questionnaires and analysis using the Mann Whitney test. From 54 respondents the duration of using surgical masks that cause with an average use of 6 hours/day and the duration of using surgical masks that do not cause with an average use of 6 hours/day. While the duration of using N95 masks that cause with an average use of 8 hours/day and the duration of using N95 masks that do not cause with an average use of 7.5 hours/day. The relationship between the use of surgical masks and the incidence of acne vulgaris obtained a p-value of 0.051 with = (p>o,o5), while the relationship between the use of N95 masks and the incidence of acne vulgaris obtained a p-value of 0.713 with = (p>o, o5). This shows that there is no significant relationship between the use of N95 masks and surgical masks on the incidence of acne vulgaris in medical personnel at Panyabungan Hospital.